EXAMINATION OF SOME PHYSICAL FITNESS CHARACTERISTICS IN 13-14 YEARS OLD FOOTBALLERS - Acar, Hakan; Tutkun, Erkut (Acta Scientiae et Intellectus, 2024)
The objective of this study is to examine some physical fitness characteristics of 13-14 years old male football players. A total of 74 children were included in the study who participated in FCBescola, Kartepe 2013 football camp. 46 of them are licensed active male football players, (n=22) 13-year-olds and (n=24) 14-year-olds who are playing in different sports clubs. 28 of them are sedentary males, (n=13) 13-year-olds and (n=15) 14-year-olds, who are living in Children Welfare Homes. Measurements of height, weight, body mass index, Illinois agility test and 30-meter sprint, flamingo balance test, grip strength and sit and reach test were carried out. The data obtained were recorded with SPSS 20 program. Independent t test was used to find out the differences between groups, while Pearson Correlation test was used to analyze the associations between the variables and the level of significance was taken as p<0.05. For 13-year-old footballer and sedentary groups the results were found as follows, respectively: body mass index (18,80±1.20 and 20,09±1,76) Illionis agility test (18,92±2,01 and 21,23±2,07 sec), 30 meter sprint (5,22±1,35 and 5,96±1,86 sec), balance (4,50±3,07 and 4,12±2,75), right hand grip (21,2±3,0 and 16,3±1,8 kg), left hand grip (17,3±3,2 and 13,9±1,2 kg), sit and reach test (22,12±3,42 and 21,76±2,96 cm), while the results were found as follows for 14-year-old footballer and sedentary groups, respectively: body mass index (19,20±1,4 and 19,56±2,19), Illionis agility test (17,75±1,85±21,20±2,02 sec), 30 meter sprint (4,99±1,12 and 5,95±1,43 sec), balance (4,20±2,87 and 4,48±2,25), right hand grip (26,3±3,2 and 17,3±1,9 kg), left hand grip 24,0±2,5 and 15,2±2,1 kg) sit and reach test (22,12±3,42 and 22,23±3,75 cm). Statistically significant differences were found between athletes and sedentary group and between 13-year-olds and 14-year-olds in terms of Illinois agility test, 30-meter sprint, right and left hand grip strength values (p<0.05). Differences were found between some physical fitness characteristics of 13 and 14 years old male football players.